Selective Nitrate Binding in Competitive Hydrogen Bonding Solvents: Do Anion-π Interactions Facilitate Nitrate Selectivity? - Watt, Michelle M.; Zakharov, Lev N.; Haley, Michael M.; Johnson, Darren W. (Angewandte Chemie International Edition, 2013)
New tripodal urea receptors demonstrate preferential binding of anions over competitive hydrogen bonding solvents. 1H NMR titrations in 10 % [D6]DMSO/CDCl3 show a higher affinity for nitrate over the halides for the fluorinated receptor, which is lost when the fluorine atoms are absent. An anion–π interaction between the nitrate and the π‐system of the ethynyl‐substituted arene is proposed as the source of this selectivity.